2017
DOI: 10.1007/s10936-017-9522-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Emotions Through Language Statistics and Embodied Cognition

Abstract: Recent research has suggested that language processing activates perceptual simulations. We have demonstrated that findings that have been attributed to an embodied cognition account can also be explained by language statistics, because language encodes perceptual information. We investigated whether comprehension of emotion words can be explained by an embodied cognition or a language statistics account. A corpus linguistic study comparing emotions words showed that words denoting the same emotions (happy-del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Emotional information has been addressed most extensively (Bestgen & Vincze, 2012; Hollis et al, 2017; Lenci, Lebani, & Passaro, 2018; Passaro et al, 2017; Recchia & Louwerse, 2015; Tillmand & Louwerse, 2018; Westbury, Keith, Briesemeister, Hofmann, & Jacobs, 2015). Bestgen and Vincze (2012) proposed a method for predicting three affective variables, that is, valence, arousal, and dominance, of ANEW norms (Bradley & Lang, 1999).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Emotional information has been addressed most extensively (Bestgen & Vincze, 2012; Hollis et al, 2017; Lenci, Lebani, & Passaro, 2018; Passaro et al, 2017; Recchia & Louwerse, 2015; Tillmand & Louwerse, 2018; Westbury, Keith, Briesemeister, Hofmann, & Jacobs, 2015). Bestgen and Vincze (2012) proposed a method for predicting three affective variables, that is, valence, arousal, and dominance, of ANEW norms (Bradley & Lang, 1999).…”
Section: Related Workmentioning
confidence: 99%
“…Recchia and Louwerse (2015) also demonstrated that PMI can predict ANEW ratings as accurately as Bestgen and Vincze's (2012) method, and Hollis et al (2017) showed that the skip‐gram model predicted them better than Recchia and Louwerse's (2015) model. Tillmand and Louwerse (2018) demonstrated that language statistics discriminated between same‐emotion and different‐emotion word pairs. Language statistics also explained reaction times required for truthfulness judgment of emotion sentences, but perceptual simulation factors did not.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The fi rst level is the level of functioning of cognitions, to which psychologists refer the main psychical processes (sensation, perception, memory, attention, which, in turn, «control» the course of cognitive activity), as well as thinking and imagination, speech and dialogical interaction (Collins, 2014;Smulson, 2003;Zasekina, 2006). The second level of intelligence is the level of metacognitions (metacognitive integrators, «secondary» mental processes), among which the main ones are intellectual initiation (self-statement of the problem), refl ection, decentralization, intellectual strategies and abilities (abilities and competences), as well as metacognitive monitoring, intuition, intellectual atheist (values, meanings) (Tillman & Louwerse, 2018). The fi rst and the second levels of intelligence, in our opinion, are fully understood by the person who carries out intellectual activity.…”
Section: Introductionmentioning
confidence: 99%
“…Embodied cognition regards the human body and the environment as significant factors in the way we think and feel (Guell, Gabrieli, & Schmahmann, 2018). This is done by processing both emotional and modality-specific systems in the brain (Barsalou et al, 2003;Niedenthal et al, 2005;Mahon, 2015;Tillman, & Louwerse, 2018), where both emotion and the sensory multi-modal specific processing of memory work together (Niedenthal, 2007;Dreyer & Pulvermüller, 2018), also known as semantic cognition (Ralph et al, 2017:2).…”
Section: Introductionmentioning
confidence: 99%